2012
DOI: 10.1007/s12028-012-9788-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-Methyl-D-Aspartate Receptor Encephalitis with Favorable Outcome Despite Prolonged Status Epilepticus

Abstract: Auto-immune encephalitis is likely underdiagnosed in adolescents. In their most severe presentation, seizures may be resistant to a large number of anti-epileptic drugs, and the clinical improvement seems to be mainly because of the immunomodulatory therapy. Relapse is possible, as well as the delayed development of a teratoma or other tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Early and reliable identification of patients with potential favorable outcome despite having SE for several days is of outmost clinical importance, as this insight may urge clinicians to intensify treatment rather than consider care withdrawal as systemic and neurologic sequelae increase, and chances of SE termination decrease over time. Good outcome is possible after prolonged treatment refractory or super‐refractory SE, with some patients returning to their premorbid status, even after >90 days of SE …”
Section: Discussionmentioning
confidence: 99%
“…Early and reliable identification of patients with potential favorable outcome despite having SE for several days is of outmost clinical importance, as this insight may urge clinicians to intensify treatment rather than consider care withdrawal as systemic and neurologic sequelae increase, and chances of SE termination decrease over time. Good outcome is possible after prolonged treatment refractory or super‐refractory SE, with some patients returning to their premorbid status, even after >90 days of SE …”
Section: Discussionmentioning
confidence: 99%
“…In children and adolescents, seizures are usually partial motor or complex seizures [6]. Even, anti-NMDAR encephalitis causes prolonged status epilepticus [50, 51], which carries a poor prognosis, with a mortality rate of 56% [52]. …”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Liu X et al reported that 22 patients with SE required ASM and anesthetics, of whom 13 patients (59.1%) had controlled SE, while another 9 patients (40.9%) had unremitting or remitting SE after reduction or discontinuation of anesthetics, relapsed and eventually died in the acute phase ( 14 ). Finné Lenoir X et al reported a case of anti-NMDAR encephalitis in a 17-year-old Asian male in whom a large number of ASMs were ineffective in his prolonged persistent epilepsy ( 16 ). In addition to conventional ASMs, Santoro et al reported ketamine as an effective adjunctive therapy for hyper refractory persistent epilepsy in patients with anti-NMDAR receptor encephalitis, suggesting that administration of a loading dose followed by maintenance infusion resulted in clinical and/or electrogram seizure cessation in less than 48 h ( 17 ).…”
Section: Resultsmentioning
confidence: 99%